1977
DOI: 10.1002/1097-0142(197706)39:6<2846::aid-cncr2820390673>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant radiotherapy trials in breast cancer

Abstract: Adjuvant radiotherapy in breast cancer according to stage of disease, present diagnostic and therapeutic advances, and the biology of the tumor is summarized: Stage I: The increasing number of small localized tumors occuring with earlier diagnosis motivates controlled clinical studies of irradiation of the breast with surgical axillary node status for exact biological classification. Encouraging results with local breast irradiation need confirmation in controlled studies. Improved survival by local interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1978
1978
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…In the 1970s it was suggested that postoperative radiotherapy could induce immune-depression leading to an increase in distant metastases (69,70). However, it was shown that the analyses were biased (71) and that induced immune changes did not have a clinical impact (72 -74).…”
Section: Toxicity Of Radiotherapymentioning
confidence: 99%
“…In the 1970s it was suggested that postoperative radiotherapy could induce immune-depression leading to an increase in distant metastases (69,70). However, it was shown that the analyses were biased (71) and that induced immune changes did not have a clinical impact (72 -74).…”
Section: Toxicity Of Radiotherapymentioning
confidence: 99%
“…Indeed if one considers only the prospectively controlled studies comparing patients who received postmastectomy radiotherapy with those who did not, nonirradiated patients as a rule fared better. This was so in eight out of ten controlled studies reviewed by Stjernsward in 1977 [57]. Only in the study reported by H@st and Brennhovt [58] was a better survival demonstrated in irradiated patients.…”
Section: Controlled Trialsmentioning
confidence: 97%
“…I was invited to a breast cancer conference later the same year, organized under the aegis of the White House, the National Cancer Institute and the American Cancer Society, and I presented all the then available results from the relevant trials. 9 In an attempt to explain the higher death rate in women treated with radiotherapy by a decrease in immuno-competent cells after irradiation, I had speculated that an increase of metastasis due to a decreased immuno-competence might explain the increased number of deaths observed in the irradiated groups. This speculation proved wrong, however.…”
Section: Reactions To the Articlementioning
confidence: 99%
“…Given our findings, engaging in discussion of statistical niceties seemed to us to be displacement activity. I was invited to a breast cancer conference later the same year, organized under the aegis of the White House, the National Cancer Institute and the American Cancer Society, and I presented all the then available results from the relevant trials 9 …”
Section: Reactions To the Articlementioning
confidence: 99%